2015
DOI: 10.1002/ejsp.2098
|View full text |Cite
|
Sign up to set email alerts
|

The effect of red on male perceptions of female attractiveness: Moderation by baseline attractiveness of female faces

Abstract: Past research has demonstrated the importance of color in a variety of social contexts, including human mating. For example, red increases heterosexual men's feelings of attraction toward women. In the current work, this basic red-attraction link is qualified by the initial attractiveness of female faces. In two experiments, red enhanced men's ratings of female attractiveness, but only for faces pre-rated as attractive; red had no influence on perceptions of initially unattractive faces. Additionally, Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…The color red has been of particular interest, and studies have shown that the meaning of the color red is context-dependent (Elliot, 2015). For example, red has been proposed to elicit feelings of attractiveness (e.g., Elliot, Greitemeyer, & Pazda, 2013;Young, 2015, but see also Lehmann & Calin-Jageman, 2017;Peperkoorn, Roberts;Pollet, 2016 for studies which do not support this specific effect of the color red). Red also shows a strong association with danger (Pravossoudovitch, Cury, Young, & Elliot, 2014).…”
Section: Context-dependency Of the Color Redmentioning
confidence: 99%
“…The color red has been of particular interest, and studies have shown that the meaning of the color red is context-dependent (Elliot, 2015). For example, red has been proposed to elicit feelings of attractiveness (e.g., Elliot, Greitemeyer, & Pazda, 2013;Young, 2015, but see also Lehmann & Calin-Jageman, 2017;Peperkoorn, Roberts;Pollet, 2016 for studies which do not support this specific effect of the color red). Red also shows a strong association with danger (Pravossoudovitch, Cury, Young, & Elliot, 2014).…”
Section: Context-dependency Of the Color Redmentioning
confidence: 99%
“…Recent research has shown that heterosexual men are more likely to rate a woman as more attractive when she is displaying red (e.g., when surrounded by red, holding something red, or wearing red clothing or lipstick; Elliot & Niesta, 2008;Gilston & Privitera, 2016;Guéguen, 2012aGuéguen, , 2012bGuéguen & Jacob, 2012a, 2012bLin, 2014;Pazda, Elliot, & Greitemeyer, 2014;Robert, Havilcek, & Owen, 2010;Stephen & McKeegan, 2010;Young, 2015). These findings are presumably due, in part, to a pervasive link between red and romance across time and cultures.…”
Section: Facial Redness Increases Men's Perceived Healthiness and Attmentioning
confidence: 99%
“…Several further experiments have corroborated the reasoning that there is a positive effect of red on attractiveness judgments, which is caused by sexual receptivity expectations (Elliot, Greitemeyer, & Pazda, ; Guéguen ; Niesta Kayser, Elliot, & Feltman, ; Pazda et al ; Young ). In accordance with these findings on red and the perceived attractiveness of others, we now propose that sexual receptivity also functions as mediator regarding the red effect on self‐attractiveness.…”
Section: Underlying Processes Of the Red Effect In The Affiliation Comentioning
confidence: 80%
“…Moreover, there is recent research on female participants indicating that women are (at least unconsciously) aware of the link between red and fertility; it was found that female participants were more inclined to wear red clothes at the peak of their fertility (Beall & Tracy, 2013). Several further experiments have corroborated the reasoning that there is a positive effect of red on attractiveness judgments, which is caused by sexual receptivity expectations (Elliot, Greitemeyer, & Pazda, 2013;Guéguen 2012;Niesta Kayser, Elliot, & Feltman, 2010;Pazda et al 2014;Young 2015). In accordance with these findings on red and the perceived attractiveness of others, we now propose that sexual receptivity also functions as mediator regarding the red effect on selfattractiveness.…”
Section: Underlying Processes Of the Red Effect In The Affiliation Comentioning
confidence: 91%